Anti-Toxoplasma Effects of Methanol Extracts of Feijoa sellowiana, Quercus castaneifolia, and Allium paradoxum - Mohammad Ali Ebrahimzadeh; Mohammad Mohammad Taheri; Ehsan Ahmadpour; Mahbobeh Montazeri; Shahabeddin Sarvi; Mohammad Akbari; Ahmad Daryani (Korean Pharmacopuncture Institute, 2017)
Objectives: The currently available agents for use against toxoplasmosis have serious limitations. Thus, the aim of the present study was to investigate the anti-Toxoplasma gondii (T. gondii) activities of methanol extracts of Feijoa sellowiana (F. sellowiana) (leaves and fruits), Quercus castaneifolia (Q. castaneifolia) (fruits), and Allium paradoxum (A. paradoxum) (leaves) in vitro and in vivo. Methods: Vero cells were treated with different concentrations (from 0 to 400 μg/mL) of the above extracts or with pyrimethamine at a dose of 50 mg/mL (positive control). Then, the viabilities of the T. gondii-infected cells were measured by using colorimetric MTT (3-(4, 5-dimethylthiazol-2-yl) 2, 5-diphenyltetrazolium bromide) assays. In addition, the survival rates of mice acutely infected with 2 × 104 RH strain tachyzoites of T. gondii were examined in vivo after intraperitoneal injection of the extracts at doses of 100 and 200 mg/kg/day for 5 days. Results: In the in vitro anti- T. gondii assay, the IC50 values were 12.77, 180.2, 74.73, 213.2 and 163.8 μg/mL, and the selectivity indices were 6.05, 1.31, 0.35, 0.69 and 1.30 for the F. sellowiana (leaves and fruits), Q. castaneifolia, and A. paradoxum extracts and pyrimethamine, respectively. Moreover, the mice treated with F. sellowiana (leaves and fruits) achieved better results in terms of survival than the others (P < 0.05). Conclusion: The results of the current study indicate that methanol extract of F. sellowiana has significant anti-Toxoplasma activity. Further study should be conducted to investigate the potential bioactivity of this extract through bioactivity-guided fractionation.